Studies on the Solute Solvent Interaction of Nimesulide in Aqueous Solutions of Hydrotropic Agents at Different Temperatures - Chandravir S. Solanki; Sushree Tripathy; Minaketan Tripathy; Upendra N. Dash (E-Journal of Chemistry)
The present study deals with experiments so as to highlight the solute (drug nimesulide) - solvent(water) interactions and related modifications in case of the presence of hydrotropic agents at different temperatures T(=298.15 to 313.15)K. Density and viscosity values of nimesulide have been determined in water in (0.1, 0.2, 0.4, 0.6, 0.8, 1 and 2) mol dm-3 aqueous solutions of hydrotropic agents (sodium benzoate, sodium salicylate, sodium bromide and nicotinamide) at temperatures 298.15, 303.15, 308.15 and 313.15 K where as the solubility was studied at 308.15 K. From the density values, the limiting partial molar volumes and expansibilities have been calculated. The experimental viscosity values have been analyzed in terms of jones-dole equation and on the basis of transition theory for relative viscosity.